Stewardship of Antibiotics for Multidrug-Resistant Gram-Negative Bacteria - Daniele Roberto Giacobbe; Ilias Karaiskos (MDPI AG, 2020)
Nearly one year ago, we wrote the following introductory note for authors willing to submit their paper to our Special Issue entitled "Stewardship of Antibiotics for Multidrug-Resistant Gram-Negative Bacteria" in Antibiotics: [...]